Dismissal, labor law and ideology (Labor and Human Development Law Journal, 2018)
In distinct historical phases, at least in three of them, Labor Law has been questioned about which discipline to apply to the dismissal or to the withdrawal. A brief reading of these three phases intends to evidence the intercurrent relations between the norm and doctrinal and jurisprudential elaborations, that is, the “legal constructions” that have accompanied their evolution. I will take into consideration the origins phase, the post-constitutional phase and obviously the current phase. I will seek to grasp the link between the ideologies of the time in order to reach the conclusion that fundamentally the key issue, which is the choice for the preferred model, is always the same and focuses itself on the recognition of asymmetry between the parties in a labor relation, particularly in the moment of withdrawal. It will be possible to observe how Labor Law, in this matter, is strongly tributary to the predominance of ideologies external to it. KEYWORDS: Labor law. Work Relations. Dismissal. Asymmetry. Ideology.